Airway compliance measurements in mouse models of respiratory diseases - Robichaud, Annette; Fereydoonzad, Liah; Collins, Samuel L.; Loube, Jeffrey Martin; Ishii, Yumiko; Horton, Maureen R.; Martin, James G.; Mitzner, Wayne (American journal of physiology. Lung cellular and molecular physiology, 2021)
The quantification of airway compliance ( C aw ) is essential to the study of airway alterations in disease models. However, the required measurements of airway pressure and volume are difficult to acquire in mice. We hypothesized that the inflation limb of full-range pressure-volume (PV) curves could be used to quantify C aw , as it contains a segment where only the airway tree is distended. The study objective was to assess the feasibility of the approach by analysis of full-range PV curves previously collected in three mouse models: an elastase model of emphysema, a genetic model spontaneously developing emphysema (leukotriene C4 synthase knockout; LTC4S-KO), and a bleomycin model of lung fibrosis. Attempts to validate results included C aw change relative to respiratory system compliance (Δ C aw /Δ C), the minute work of breathing (mWOB), and the elastance at 20.5 Hz ( E rs _20.5) from prior respiratory mechanics measurements in the same subjects. C aw was estimated at 3% of total compliance in healthy mice or 2.3 ± 1 μL/cmH 2 O ( n = 17). The technique detected changes in models of respiratory obstructive and restrictive diseases relative to control mice as well as differences in the two emphysema models studied. The changes in C aw were consistent with those seen in Δ C aw /Δ C, mWOB, or E rs _20.5, with some variations according to the model, as well as with results reported in the literature in humans and mice. Direct C aw measurements in subjects as small as mice could prove useful to further characterize other respiratory disease models associated with airway remodeling or to assess treatment effects.